Culture Shock with Subjective Well-Being in Overseas Students - Rahmayanti, Siti; Setyaningtyas, Angelina Dyah Arum (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Environmental differences are one of the difficulties faced by overseas students. Individuals need to adapt hard to be able to compensate. When the conditions in the new environment are not successful, it will cause many negative responses, such as being dissatisfied with life, experiencing high negative emotions, and experiencing low positive emotions. The response to this situation is known as culture shock. This negative response can lower the level of subjective well-being in individuals. This study aims to determine whether there is a relationship between culture shock and the subjective well-being of overseas students. This research involved 174 overseas students aged 18-25 years. This research uses the satisfaction with life scale (SWLS), positive effect negative affect schedule (PANAS) scale, and culture shock scale. The research data were analyzed using the data collection method based on the Likert scale and analyzed using the product-moment correlation. The results of the correlation analysis showed that there was a negative relationship between culture shock and subjective well-being in overseas students, with a correlation value (rxy) of r=0.228 and p=0.002 (p <0.05). This shows that the hypothesis in the study is accepted. These findings indicate that culture shock can affect the subjective well-being of overseas students.